TEMPLE REPRESENTATION IN THE ARCHITECTURE OF HIGHRISE BUILDINGS OF THE REFORMATION ERA IN JAKARTA - Muhammad Hilmy Arieza ; Rahadhian P. Herwindo (Riset Arsitektur (RISA), 2018)
Abstract - Temples are one of the most important cultural archeological remains available in Indonesia. Over the centuries and indeed up to the present, the various elements in the design of temples have been considered as a reference point and the origin of architecture in Indonesia. The Prambanan temple constitutes the first highrise building in South East Asia, which serves to prove that in that particular era, the ancestors of the current Indonesian population were able to inspire the world with its creations. The temples spread all over Indonesia can be labelled unique because they differed from those hailing from the source of inspiration, namely the country of India. This was due to the active role played by the local genius at that point in time, which showed a knack for absorbing foreign concepts while simultaneously selecting and adapting these ideas to the Indonesian context. In keeping with the developments typical of the era and the available technology, exploring the cultural wealth of resources and architecture must be continued as a matter of course; if not, there is cause for alarm that the local values and the very identity of Indonesian architecture may well fade, and all the more so in the reformation era typified by the increasingly dominant current of globalization. The most rapid development can be found in Jakarta as Indonesia’s capital and the melting pot of all aspects. The density of this urban population goes up all the time, and the price of the increasingly rare land available has followed suit. This particular trend has driven the vertical expansion for reasons of efficient land use and economic factors. The expansion level of high-rise buildings in Jakarta has also risen sharply due to the increasing need. These high-rise buildings can be considered as a symbol of a strong economy of a given city because they define the urban skyline and form a source of pride for the city dwellers. Allowing this expansion of high-rise buildings without making a rigorous selection has frequently led to the urban skyline’s loss of character, and a regrettable tendency to look identical to the skyline of other cities. The purpose of this research project is to study the use of temple representation in the architecture of high-rise buildings of the Reformation Era in Jakarta by way of examining the architectural works of PT Arkonin & PT Airmas Asri. Keywords : Temple, reformation, local genius, high-rise building, representation